Agenda For a New Economy : From Phantom Wealth to Real Wealth - Korten, David C. (New Delhi Tata Mcgraw-Hill Publishing Company, 2009)
Agenda for the New Economy provides the most fundamental and far-reaching critique yet published of what is really wrong in our economic system and the path forward to creating a new economic system that better meets human needs. This Second Edition updates the arguments and information throughout the book in the light of developments in 2009, and it offers a new chapter that shows how the 2009 programs of the Obama administration and other governments are not getting at the root causes of the system failures nor making the deep changes that are needed if we are to avoid ongoing economic, soc.
Keywords: United States -- Economic policy -- Economic history